Pengaruh Minat Belajar, Gaya Belajar, dan Kemampuan Berpikir Kreatif terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Dasar Desain Grafis di SMK PGRI 2 Malang - Dian Agus Sasmita; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
This research is motivated by the learning outcomes of Grade X SMK PGRI 2 Malang which is less maximum. The purpose of this research is to know the influence of learning interest, learning style, and creative thinking ability to study results of grade X students on Basic Graphic Design subjects at SMK PGRI 2 Malang. This study used quantitative approaches with the expost facto research type. The retrieval of learning interest and learning styles uses questionnaires and creative thinking skills using assessment, while the result data is learned from the final value of 2020/2021 school students. The samples in this study were students of Grade X Computer Engineering Network and Multimedia SMK PGRI 2 Malang. The results of this study showed that interest in learning had no effect on learning outcomes with a significant value of 0.668 > 0.05. Learning style has no effect on learning outcomes with a significant value of 0.272 > 0.05. Creative thinking skills have no effect on learning outcomes with signification value 0.643 > 0.05. Learning interests, learning styles, and creative thinking skills have no effect on learning outcomes with a significant value of 0.72 > 0.05.